Formant Analysis of Vowels in Kurdish Language - Dinler, Ozlem Batur; Karabiber, Fatih (IEEE, 2017)
In this study, formant analysis of the Kurdish language spoken in Turkey was examined. In order to analyze acoustic features of Kurdish vowels, speech recording is collected from 40 adults who knows how to read and write in Kurdish. A statistical and visual analysis of the formant frequencies of the isolated speeches obtained from these records was performed. In statistic analysis formant frequency values of the speech signal is calculated by LPC method. In the visual analysis, the spectrum and formant value graphs of the speech signal is covered. As a result of this study, the articulation model of the Kurdish speech system with the vowel phonemes in Kurdish was introduced and the acoustic property of the Kurdish was revealed. Since there is a few study about Kurdish, this study will contribute in the field of Kurdish.
Keywords: speech processing; Kurdish; phonetic feature; formant frequency analysis; Lpc; Praat; Acoustics; Computer Science; Engineering; Telecommunications